Finansal Hizmetlere Erişim ve Sürdürülebilir Kalkınma - (:unkn) unknown (My University, 2017)
Finansal hizmetlere erişim, bir toplumun gelişimi için oldukça önemlidir. Ülkelerin teknolojik, sosyolojik ve ekonomik gelişimleri; bu ülkelerde yaşayanların finansal kaynaklara erişiminin uygunluğu ile de bağlantılıdır. Finansal kaynaklara erişim, kalkınmanın da sürdürülebilir olmasına fırsat doğuracaktır. Çalışmada Türkiye'de finansal hizmetlere erişim ve sürdürülebilir kalkınma ilişkisi tartışılmaktadır

Access to financial services is very important for the development. The technological, sociological and economic development of countries is also linked to the appropriateness of access to financial resources for those living in these countries. Access to financial resources will provide opportunities for the sustainability of development. In this study, the relationship between access to financial services and sustainable development in Turkey is being discussed
Access to Financial Services and Sustainable Development
Keywords: İşletme Finans; İşletme